Positive electrode active material, positive electrode, and lithium secondary battery

By guiding the growth of primary particles of lithium manganese oxide positive electrode material and sharing different aluminum elements, the problems of unstable electrochemical performance and frequent side reactions under high pressure conditions are solved, and higher electrochemical performance and stability are achieved.

JP2025071125AActive Publication Date: 2025-05-02ECOPRO BM CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2025022984
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-10-27
Filing Date
2025-02-17
Publication Date
2025-05-02
Estimated Expiration
2043-05-29

AI Technical Summary

Technical Problem

The lithium-extra-lithium-manganese oxide positive electrode active materials in existing lithium-ion secondary batteries have problems of unstable electrochemical performance and frequent side reactions under high-voltage driving conditions, resulting in a decline in battery performance.

Method used

By guiding the growth of primary particles of lithium manganese oxide in the positive electrode material, particles of different shapes are formed, and different elements of co-aluminum are used to reduce the gap between the particles, thereby reducing the side reaction between the positive electrode material and the electrolyte.

Benefits of technology

It improves the electrochemical performance and stability of lithium manganese oxide positive electrode material, reduces side reactions under high-voltage conditions, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025071125000001
    Figure 2025071125000001
  • Figure 2025071125000002
    Figure 2025071125000002
  • Figure 2025071125000003
    Figure 2025071125000003
Patent Text Reader

Abstract

To provide a positive electrode active material that can prevent abrupt degradation in battery performance due to side reactions in an initial battery reaction under a high-voltage condition by reducing a specific surface area of a lithium manganese-based oxide.SOLUTION: A positive electrode active material comprises a lithium manganese-based oxide in which a phase belonging to the C2 / m space group and a phase belonging to the R3-m space group are dissolved or complexed. The lithium manganese-based oxide comprises a secondary particle formed by aggregating a plurality of primary particles. The lithium manganese-based oxide comprises at least one selected from tungsten, molybdenum and niobium as a dopant. At least some of oxygen present in the lithium manganese-based oxide is substituted with halogen. An interparticle porosity between the primary particles, measured from a cross-sectional SEM image of the secondary particle, is 10% or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a positive electrode active material, a positive electrode, and a lithium secondary battery including the same. More specifically, the present invention relates to a positive electrode active material including a lithium-excess lithium-manganese-based oxide, which can prevent a decrease in electrochemical characteristics of a lithium secondary battery, including rate characteristics, caused by excess lithium and manganese in the lithium manganese-based oxide, by inducing growth of primary particles constituting the lithium manganese-based oxide, and can reduce side reactions between the lithium manganese-based oxide and an electrolyte during high voltage operation. The present invention also relates to a positive electrode active material, a positive electrode, and a lithium secondary battery including the same.

[0002] Batteries store electricity by using materials capable of electrochemical reaction at the positive and negative electrodes. A representative example of such batteries is a lithium secondary battery, which stores electrical energy by the difference in chemical potential when lithium ions are intercalated / deintercalated at the positive and negative electrodes.

[0003] The lithium secondary battery is manufactured by using a material capable of reversible intercalation / deintercalation of lithium ions as a positive electrode active material and a negative electrode active material, and filling an organic electrolyte or a polymer electrolyte between the positive electrode and the negative electrode.

[0004] Representative materials used as positive electrode active materials for lithium secondary batteries include lithium composite oxides, such as LiCoO2, LiMn2O4, LiNiO2, LiMnO2, and oxides of Ni, Co, Mn, Al, etc.

[0005] Among the positive electrode active materials, LiCoO2 is the most widely used because of its excellent life characteristics and charge / discharge efficiency. However, it has a drawback in that it is expensive due to the limited availability of cobalt as a raw material, and therefore has limited price competitiveness.

[0006] Lithium manganese oxides such as LiMnO2 and LiMn2O4 have the advantages of being thermally safe and inexpensive, but have problems with small capacity and poor high-temperature characteristics. In addition, LiNiO2-based positive electrode active materials show high discharge capacity battery characteristics, but are difficult to synthesize due to the problem of cation mixing between Li and transition metals, which causes major problems with rate characteristics.

[0007] In addition, a large amount of Li by-products are generated depending on the depth of the cation mixing. The Li by-products mostly contain LiOH and Li2CO3, which may cause gelation during the preparation of the positive electrode paste or gas generation due to repeated charging and discharging after the electrode is manufactured. In addition, the remaining Li2CO3 among the Li by-products increases the swelling phenomenon of the cell, thereby reducing the life characteristics.

[0008] To overcome these shortcomings of conventional positive electrode active materials, various candidate materials have been proposed.

[0009] For example, research is being conducted to use lithium-rich lithium manganese oxides, which contain an excess amount of Mn among transition metals and have a lithium content greater than the total content of the transition metals, as a positive electrode active material for lithium secondary batteries. Such lithium-rich lithium manganese oxides are also called overlithiated layered oxides (OLO).

[0010] Although OLO has an advantage of theoretically being able to exhibit high capacity under a high voltage operating environment, in practice, it has a disadvantage of having relatively low electrical conductivity due to the excessive amount of Mn contained in the oxide, which results in low rate characteristics of lithium secondary batteries using OLO. Such low rate characteristics cause problems such as reduced charge / discharge capacity and life efficiency (capacity retention) during charge / discharge cycles of the lithium secondary battery.

[0011] In addition, the decrease in charge / discharge capacity or voltage decay during charge / discharge cycles of a lithium secondary battery using OLO may be induced by a phase transition caused by the movement of transition metals in the lithium manganese oxide. For example, when a phase transition is induced by the movement of transition metals in an unintended direction in a lithium manganese oxide having a layered crystal structure, a spinel or similar crystal structure may be generated entirely and / or partially in the lithium manganese oxide.

[0012] In order to solve the above problems, research has been conducted into modifying the composition of OLO, but these attempts have not yet reached a commercial level. Summary of the Invention [Problem to be solved by the invention]

[0013] In the lithium secondary battery market, the growth of lithium secondary batteries for electric vehicles is playing a leading role in the market, and as a result, the demand for positive electrode active materials used in lithium secondary batteries is also continuously increasing.

[0014] For example, in the past, lithium secondary batteries using lithium iron phosphate (LFP) were mainly used from the perspective of ensuring safety, but recently there has been a trend toward expanding use of nickel-based lithium composite oxides, which have a larger energy capacity per weight than LFP.

[0015] In addition, nickel-based lithium composite oxides, which are currently mainly used as positive electrode active materials for high-capacity lithium secondary batteries, essentially use ternary metal elements such as nickel, cobalt, and manganese or nickel, cobalt, and aluminum. However, since the supply and demand of cobalt is unstable and it is excessively expensive compared to other raw materials, a new positive electrode active material with a reduced or eliminated cobalt content is needed.

[0016] Considering these various circumstances, lithium-excess lithium manganese-based oxides can meet the above-mentioned market expectations, but the lithium manganese-based oxides still have limitations in that their electrochemical properties and stability are insufficient as an alternative to commercialized positive electrode active materials such as nickel-cobalt-manganese (NCM) or nickel-cobalt-aluminum (NCA) ternary lithium composite oxides.

[0017] For example, as described above, if a transition metal in a lithium manganese oxide moves in an unintended direction, and a spinel or similar crystal structure is formed entirely and / or partially in the lithium manganese oxide, a reduction in charge / discharge capacity or voltage decay may occur during charge / discharge cycles of a lithium secondary battery using OLO.

[0018] However, when compared with other types of commercially available positive electrode active materials, the conventional lithium-excess lithium manganese-based oxide has disadvantages in terms of electrochemical properties and / or stability. However, the present inventors have confirmed that the lithium-excess lithium manganese-based oxide can also exhibit electrochemical properties and stability at a level that allows it to be commercially available by inducing the growth of primary particles constituting the lithium manganese-based oxide so that the primary particles have a different shape than conventional ones.

[0019] Accordingly, the present invention provides a positive electrode active material including a lithium-excess lithium-manganese-based oxide, in which the growth of primary particles constituting the lithium manganese-based oxide is induced so that the primary particles constituting the lithium manganese-based oxide have a different shape from that of previously known lithium manganese-based oxides.

[0020] In particular, the present invention aims to provide a cathode active material capable of reducing the specific surface area of ​​the lithium manganese-based oxide by inducing the growth of primary particles constituting the lithium manganese-based oxide, thereby preventing a rapid decrease in battery performance due to side reactions during an initial battery reaction under high voltage conditions.

[0021] Another object of the present invention is to provide a cathode active material capable of improving electrochemical properties of the lithium manganese-based oxide composed of primary particles by inducing growth of the primary particles constituting the lithium manganese-based oxide while co-doping different elements.

[0022] Another object of the present invention is to provide a lithium secondary battery that can prevent deterioration in electrochemical characteristics of a lithium secondary battery, including rate characteristics, caused by excessive amounts of lithium and manganese conventionally present in OLO, by using a positive electrode including the positive electrode active material defined herein, and can achieve high stability by reducing side reactions between the positive electrode active material and an electrolyte during high voltage operation. [Means for solving the problem]

[0023] According to one aspect of the present invention for solving the above-mentioned technical problems, there is provided a positive electrode active material including a lithium manganese-based oxide in which a phase belonging to the C2 / m space group and a phase belonging to the R3-m space group are dissolved or combined.

[0024] Generally, commercially available ternary lithium composite oxides having a nickel-cobalt-manganese (NCM) or nickel-cobalt-aluminum (NCA) composition have a single phase of a phase belonging to the R3-m space group, whereas the lithium-rich lithium manganese oxide defined in the present application is characterized by a solid solution or composite of a phase belonging to the C2 / m space group and a phase belonging to the R3-m space group.

[0025] In an embodiment, the lithium manganese-based oxide includes secondary particles formed by agglomeration of a plurality of primary particles.

[0026] In this case, when the oxide precursor of the lithium manganese-based oxide is calcined, the growth of the primary particles is induced and the oxide precursor is simultaneously doped with a different element, thereby forming a specific shape of the primary particles constituting the lithium manganese-based oxide.

[0027] Here, the lithium manganese-based oxide may contain at least one selected from tungsten, molybdenum, and niobium as a dopant, and at least a portion of oxygen present in the lithium manganese-based oxide may be substituted with a halogen.

[0028] The average minor axis length of the primary particles constituting the lithium manganese oxide may be 160 nm or more, preferably 160 nm or more and 500 nm or less, and more preferably more than 210 nm and 400 nm or less.

[0029] The average minor axis length of the primary particles can be measured for the primary particles exposed on the surface of the secondary particles from the SEM image of the secondary particles (for example, calculated from 20 primary particles selected in order of the longest minor axis length from among the primary particles exposed on the surface of the secondary particles from the SEM image of the secondary particles).

[0030] In addition, the interparticle porosity between the primary particles measured from a cross-sectional SEM image of the secondary particles formed by aggregation of the primary particles may be 10% or less, preferably 5% or less.

[0031] The lithium manganese-based oxide may be a lithium-excess lithium manganese-based oxide represented by the following Chemical Formula 1.

[0032] [Chemical formula 1] rLi2MnO 3-b′ X′ b′ (1-r)Lia M1 x M2 y M3 z O 2-b X b (Here, M1 is at least one selected from Ni and Mn, M2 is at least one selected from Ni, Mn, Co, Al, P, Nb, B, Ti, Zr, Ba, K, Mo, Si, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, V, Ta, Sn, Hf, Ce, Gd, and Nd, M3 is at least one selected from W, Mo, and Nb, M1 to M3 do not overlap with each other, X and X′ are halogens capable of substituting at least a part of the oxygen present in the lithium manganese-based oxide, 0 < r ≤ 0.7, 0 < a ≤ 1, 0 ≤ b ≤ 0.1, 0 ≤ b′ ≤ 0.1, 0 < x ≤ 1, 0 ≤ y < 1, 0 < z ≤ 0.1, and 0 < x + y + z ≤ 1, provided that b and b′ are not simultaneously 0.)

[0033] At least a part of the oxygen present in the lithium manganese-based oxide may be substituted with a halogen, preferably fluorine. Specifically, the primary particles may be doped with fluorine.

[0034] It is preferable that M3 and a halogen (for example, fluorine) are doped into the primary particles while inducing the growth of the primary particles during the firing of the oxide precursor of the lithium manganese-based oxide.

[0035] According to another aspect of the present invention, a positive electrode containing the above-described positive electrode active material is provided.

[0036] According to still another aspect of the present invention, a lithium secondary battery using the above-described positive electrode is provided.

Advantages of the Invention

[0037] According to the present invention, it is possible to improve the limitations of conventional lithium-rich lithium manganese oxides, which have various disadvantages in terms of electrochemical properties and / or stability, when compared with commercially available ternary lithium composite oxides having a nickel-cobalt-manganese (NCM) or nickel-cobalt-aluminum (NCA) composition.

[0038] Specifically, the growth of the primary particles constituting the lithium manganese-based oxide according to the present invention can be induced to have a shape different from that of the primary particles constituting the lithium manganese-based oxides known so far. As such, according to the present invention, the primary particles are made to have a shape different from that of the conventional primary particles, so that the lithium-excess lithium manganese-based oxide can exhibit electrochemical properties and stability at a level that allows it to be commercially used.

[0039] First, when inducing the growth of primary particles constituting the lithium manganese-based oxide, the specific surface area of ​​the lithium manganese-based oxide can be reduced, thereby preventing a rapid decrease in battery performance due to side reactions during the initial battery reaction under high voltage conditions.

[0040] When the specific surface area of ​​the lithium manganese-based oxide is reduced, it is possible to reduce side reactions between the lithium manganese-based oxide and the electrolyte. In particular, OLO, such as the lithium manganese-based oxide, has an advantage of exhibiting high capacity under a high voltage operating environment, but the possibility of side reactions between the lithium manganese-based oxide and the electrolyte may increase as the operating voltage increases, so it is important to reduce side reactions between the lithium manganese-based oxide and the electrolyte.

[0041] Therefore, the side reaction between the lithium manganese-based oxide and the electrolyte is reduced, thereby improving the stability and lifespan of a lithium secondary battery using the lithium manganese-based oxide as a positive electrode active material. In particular, the positive electrode active material with reduced side reactions with the electrolyte can operate the lithium secondary battery at a higher voltage.

[0042] In addition, as described above, when inducing the growth of the primary particles, the interparticle porosity between the primary particles forming the secondary particles can be reduced by co-doping with different elements. In this way, when the porosity in the lithium manganese-based oxide is reduced, the capacity per unit volume can be increased, thereby compensating for the insufficient electrochemical properties of the positive electrode active material including the lithium manganese-based oxide.

[0043] In particular, when inducing the growth of the primary particles, the capacity and rate characteristics of the lithium manganese-based oxide can be improved depending on the doped element.

[0044] In this manner, when a positive electrode including the positive electrode active material defined in the present application is used, it is possible to prevent the deterioration of electrochemical characteristics of a lithium secondary battery, including rate characteristics, caused by excess lithium and manganese conventionally present in OLO, and to achieve high stability by reducing side reactions between the positive electrode active material and an electrolyte during high voltage operation.

[0045] In addition to the above-mentioned effects, specific effects of the present invention will be described below together with specific matters for carrying out the invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0046] In order to make the present invention easier to understand, certain terms are defined herein for convenience. Unless otherwise defined herein, scientific and technical terms used in the present invention shall have the meanings commonly understood by those of ordinary skill in the art. Furthermore, unless otherwise specified by the context, singular terms shall be understood to include their plural forms, and plural terms shall be understood to include their singular forms.

[0047] Hereinafter, a positive electrode active material including a lithium-excess lithium manganese-based oxide according to some embodiments of the present invention and a lithium secondary battery including the positive electrode active material will be described in more detail.

[0048] positive electrode active material According to one aspect of the present invention, there is provided a positive electrode active material comprising a lithium manganese-based oxide in which a phase belonging to the C2 / m space group and a phase belonging to the R3-m space group are dissolved or combined.

[0049] The lithium manganese-based oxide contains at least lithium, nickel, and manganese. In this case, the lithium manganese-based oxide is also called an overlithiated layered oxide (OLO) because the lithium content in the lithium manganese-based oxide is greater than the total content of other transition metals (generally, the molar ratio of lithium to all metal elements other than lithium in the lithium manganese-based oxide (Li / Metal molar ratio) is greater than 1).

[0050] In general, in a commercially available ternary lithium composite oxide having a nickel-cobalt-manganese (NCM) or nickel-cobalt-aluminum (NCA) composition, the manganese content of all metal elements excluding lithium is 20 mol % or less. In consideration of this, the lithium manganese-based oxide has a relatively high ratio of manganese (e.g., 50 mol % or more, preferably 55 mol % to 75 mol %) among all metal elements compared to a commercially available ternary lithium composite oxide.

[0051] In addition, considering that commercially available ternary lithium composite oxides having a nickel-cobalt-manganese (NCM) or nickel-cobalt-aluminum (NCA) composition have a nickel content of 60 mol% or more (80 mol% or more in the case of high-Ni type) among all metal elements excluding lithium, the lithium manganese-based oxide has a relatively low ratio of nickel among all metal elements (e.g., less than 50 mol%, preferably 25 mol% to 45 mol%) compared to commercially available ternary lithium composite oxides.

[0052] There is also a difference in that the Li / Metal molar ratio measured from the lithium manganese-based oxide defined in the present application is larger than that of ternary lithium composite oxides such as nickel-cobalt-manganese (NCM) or nickel-cobalt-aluminum (NCA). For example, the Li / Metal molar ratio of ternary lithium composite oxides such as nickel-cobalt-manganese (NCM) or nickel-cobalt-aluminum (NCA) has a value close to 1. On the other hand, the Li / Metal molar ratio of the lithium manganese-based oxide defined in the present application is larger than 1, preferably 1.1 to 1.7, more preferably 1.2 to 1.6.

[0053] Despite the above-mentioned differences in composition, the lithium manganese-based oxide can also function as a composite metal oxide capable of intercalating / deintercalating lithium ions.

[0054] The lithium manganese-based oxide included in the positive electrode active material defined herein includes secondary particles formed by agglomeration of a plurality of primary particles, and the lithium manganese-based oxide may partially exist as one primary particle, i.e., a single particle.

[0055] The primary particles constituting the lithium manganese-based oxide may have various shapes within the range defined herein.

[0056] Conventional lithium-rich lithium manganese oxides have a secondary particle form in which a plurality of primary particles are aggregated, and generally have a form in which primary particles having an average particle size of several to several tens of nm are aggregated.

[0057] On the other hand, according to the present invention, the growth of the primary particles is induced, so that the primary particles constituting the lithium manganese-based oxide may have an average particle size of 0.1 μm to 5 μm, preferably 0.1 μm to 1.0 μm, and more preferably 0.25 μm to 0.75 μm.

[0058] The long axis length of the primary particles, the short axis length of the primary particles, the ratio of the long axis length to the short axis length of the primary particles (long axis length / short axis length), and the average particle size of the primary particles ([long axis length+short axis length] / 2) can be calculated as the average value of the long axis length and short axis length of the primary particles exposed on the surface of the secondary particles.

[0059] For example, the average value of the results measured from all primary particles exposed on the surface of the secondary particle or the average value of the results measured from a plurality of primary particles selected from the primary particles exposed on the surface of the secondary particle (for example, or calculated from a plurality of primary particles (e.g., 10 primary particles, 20 primary particles, etc.) selected in order of the longest minor axis length from the primary particles exposed on the surface of the secondary particle from an SEM image of the secondary particle) can be used.

[0060] When the average particle size of the primary particles is less than 0.1 μm, the specific surface area of ​​the lithium manganese oxide (secondary particles) composed of the primary particles is relatively large, and in this case, the lithium manganese oxide and the electrolyte are more likely to cause a side reaction during storage or operation of the lithium secondary battery.

[0061] On the other hand, when the average particle size of the primary particles is larger than 5 μm, the growth of the primary particles is excessively induced, and the diffusion path of the lithium ions in the primary particles is also lengthened. When the diffusion path of the lithium ions in the primary particles is excessively long, the mobility of the lithium ions in the primary particles and the diffusion of the lithium ions through the primary particles are reduced, which causes the resistance of the lithium manganese oxide (secondary particles) composed of the primary particles to increase.

[0062] In order to reduce the specific surface area of ​​the lithium manganese oxide and at the same time prevent a decrease in the mobility of lithium ions within the primary particles and the diffusibility of lithium ions through the primary particles, the average particle size of the primary particles is preferably 0.1 μm to 5 μm, more preferably 0.1 μm to 1.0 μm, even more preferably 0.25 μm to 0.75 μm, and particularly preferably 0.40 μm to 0.65 μm.

[0063] According to the present application, when the primary particles constituting the lithium manganese oxide satisfy the definition of the minor axis length described below on the premise that the primary particles satisfy the above-mentioned range of average particle diameter (more preferably, when the primary particles simultaneously satisfy the definitions of the minor axis length and the major axis length described below on the premise that the primary particles satisfy the above-mentioned range of average particle diameter), the specific surface area of ​​the primary particles can be effectively reduced within a range that alleviates the decrease in the diffusibility of lithium ions mediated by the primary particles.

[0064] The average minor axis length of the primary particles calculated from the primary particles constituting the lithium manganese-based oxide may be 160 nm or more, preferably 160 nm to 500 nm, more preferably 210 nm to 400 nm. As described above, the average minor axis length of the primary particles may be the average minor axis length measured from all primary particles exposed on the surface of the secondary particles or a plurality of primary particles (e.g., 10 primary particles, 20 primary particles, etc.) selected in order of the longest minor axis length from among the primary particles exposed on the surface of the secondary particles.

[0065] When the average minor axis length of the primary particles is less than 160 nm, the specific surface area of ​​the lithium manganese-based oxide (secondary particles) composed of the primary particles becomes relatively large, and the lithium manganese-based oxide is more likely to undergo a side reaction with the electrolyte during storage or operation of the lithium secondary battery.

[0066] In addition, from the viewpoint of reducing the deviation of the minor axis length of the primary particles exposed on the surface of the secondary particles, the minimum value of the minor axis length measured for the primary particles exposed on the surface of the secondary particles may be 80 nm or more, preferably 100 nm to 300 nm, more preferably 160 nm to 250 nm, and the maximum value of the minor axis length measured for the primary particles exposed on the surface of the secondary particles may be 1 μm or less, preferably 230 nm to 1 μm, more preferably 250 nm to 800 nm. The smaller the deviation of the minor axis length of the primary particles exposed on the surface of the secondary particles, the more uniform the surface kinetic of the secondary particles can be maintained.

[0067] The average minor axis length of the primary particles being greater than 500 nm means that the growth of the primary particles constituting the secondary particles is generally induced excessively, and the unnecessary promotion of the growth of the primary particles may reduce the mobility of lithium ions within the primary particles and the diffusion of lithium ions through the primary particles.

[0068] In addition, the average value of the major axis length of the primary particles calculated from the primary particles constituting the lithium manganese-based oxide may be 570 nm or more, preferably 570 nm to 1 μm, more preferably 600 nm to 820 nm. As described above, the average value of the major axis length of the primary particles may be the average value of the major axis length measured from all primary particles exposed on the surface of the secondary particles or a plurality of primary particles (e.g., 10 primary particles, 20 primary particles, etc.) selected in order of the longest minor axis length from among the primary particles exposed on the surface of the secondary particles.

[0069] When the average major axis length of the primary particles is less than 570 nm, the specific surface area of ​​the lithium manganese-based oxide (secondary particles) composed of the primary particles becomes relatively large, and the lithium manganese-based oxide and the electrolyte are likely to cause a side reaction during storage or operation of the lithium secondary battery.

[0070] In addition, from the viewpoint of reducing the deviation of the major axis length of the primary particles exposed on the surface of the secondary particles, the minimum value of the major axis length measured for the primary particles exposed on the surface of the secondary particles may be 245 nm or more, preferably 245 nm to 450 nm, and the maximum value of the major axis length measured for the primary particles exposed on the surface of the secondary particles may be 1.5 μm or less, preferably 880 nm to 1.5 μm, more preferably 920 nm to 1.3 μm. The smaller the deviation of the major axis length of the primary particles exposed on the surface of the secondary particles, the more uniform the surface kinetic of the secondary particles can be maintained.

[0071] The average major axis length of the primary particles being greater than 1 μm means that the growth of the primary particles constituting the secondary particles is generally induced excessively, and the unnecessary promotion of the growth of the primary particles may reduce the mobility of lithium ions within the primary particles and the diffusion of lithium ions through the primary particles.

[0072] In addition, if the length of the major axis in the primary particles is excessively long, the diffusion path of the lithium ions in the primary particles becomes excessively long, and the diffusibility of the lithium ions through the primary particles decreases, and the resistance of the primary particles increases. In addition, the possibility of a polarization phenomenon occurring in the primary particles increases. If the polarization phenomenon in the primary particles deepens, the possibility of cracks occurring in the primary particles may increase.

[0073] When the lithium manganese-based oxide exists as secondary particles formed by agglomeration of a plurality of primary particles, the secondary particles may have an average particle size ([long axis length + short axis length] / 2) of 0.5 μm to 15 μm. The average particle size of the secondary particles may vary depending on the number of the primary particles constituting the secondary particles. In addition, as the growth of the primary particles is induced to increase the average particle size of the primary particles, the number of the primary particles constituting the secondary particles may decrease.

[0074] In this way, the growth of the primary particles constituting the lithium manganese-based oxide defined herein is induced, so that the specific surface area is reduced overall. As a result, the lithium manganese-based oxide achieves sufficient surface kinetics and at the same time improves surface stability, thereby reducing side reactions between the lithium manganese-based oxide and the electrolyte. As a result, early deterioration of the positive electrode active material including the lithium manganese-based oxide defined herein can be prevented, and further, the life of the lithium secondary battery using the positive electrode active material can be improved.

[0075] There are various methods for inducing the growth of the primary particles in the lithium manganese-based oxide, but the intended effect of the present application may not be achieved depending on the difference in the method for inducing the growth of the primary particles. According to the present invention, a method is used in which the oxide precursor of the lithium manganese-based oxide is doped with a different element while inducing the growth of the primary particles when the oxide precursor of the lithium manganese-based oxide is calcined. However, even if doping is induced when the hydroxide precursor of the lithium manganese-based oxide or the oxide precursor of the lithium manganese-based oxide is calcined, the intended effect of crystal growth of the present application may not be achieved, so a detailed explanation of this is provided below with reference to the experimental examples.

[0076] The lithium manganese-based oxide defined herein may be a lithium-excess lithium manganese-based oxide represented by the following Chemical Formula 1:

[0077] [Chemical formula 1] rLi2MnO 3-b′ X′ b′ (1-r)Li a M1 x M2 y M3 z O 2-b X b Where: M1 is at least one selected from Ni and Mn; M2 is at least one selected from Ni, Mn, Co, Al, P, Nb, B, Ti, Zr, Ba, K, Mo, Si, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, V, Ta, Sn, Hf, Ce, Gd, and Nd, M3 is at least one selected from W, Mo, and Nb, M1 to M3 do not overlap with each other, X and X′ are halogens capable of substituting at least a part of the oxygen present in the lithium manganese-based oxide, where 0 < r ≦ 0.7, 0 < a ≦ 1, 0 ≦ b ≦ 0.1, 0 ≦ b′ ≦ 0.1, 0 < x ≦ 1, 0 ≦ y < 1, 0 < z ≦ 0.1, and 0 < x + y + z ≦ 1, provided that b and b′ are not simultaneously 0.

[0078] In the case where M1 is Ni in the chemical formula 1, M2 may contain Mn, and in the case where M1 is Mn, M2 may contain Ni. Also, in the case where M1 is Ni and Mn, M2 may not exist, or if it exists, it may be an element other than Ni and Mn.

[0079] Among the lithium manganese-based oxides represented by the chemical formula 1, different dopants are represented as M3 and X. M3 is at least one selected from W, Mo, and Nb, and may contain a plurality of elements selected from W, Mo, and Nb as necessary.

[0080] The types of halogens that can be used as X and X′ can be referred to the periodic table, and F, Cl, Br, and / or I can be used, and preferably, F can be used.

[0081] As described above, when inducing the growth of the primary particles constituting the lithium manganese-based oxide and doping with a halogen, preferably, at least a part of the oxygen present in the lithium manganese-based oxide may be substituted with a halogen.

[0082] When a thermal treatment is performed at a relatively high temperature without doping a halogen in order to induce the growth of the primary particles constituting the lithium manganese-based oxide, the primary particles can grow, but the crystal structure of the primary particles may be damaged, which may cause early deterioration of the positive electrode active material.

[0083] When fluorine is used as an anion dopant during the growth of the primary particles, the growth of the primary particles can be induced within a range that alleviates a decrease in the diffusibility of lithium ions through the primary particles.

[0084] For fluorine doping of the primary particles, at least one anion dopant selected from LiF, MgF2, HF, F2, XeF2, TbF4, CeF4, CoF3, AgF2, MoF3, AgF, CuF2, FeF3, CuF, VF3, CrF3, ZrF4, BaF2, CaF2, AlF3, NH4F, CeF3 and CsF, preferably at least one anion dopant selected from LiF and MgF2, can be used.

[0085] The content of fluorine doped in the primary particles can be predicted from the content of fluorine in the lithium manganese oxide represented by Formula 1 (i.e., the values ​​of b and b' in Formula 1). In addition, when neither b nor b' in Formula 1 is 0, b+b' may be 0.2 or less, preferably 0.1 or less.

[0086] When the oxide precursor is calcined, in addition to the anion dopant, a M3-containing dopant is further used to induce simultaneous doping, so that the primary particles can grow closer to a sphere instead of growing in a plate shape.

[0087] As the M3-containing dopant, at least one selected from the group consisting of hydroxides, oxides, carbonates, nitrides, sulfides, and phosphates containing at least one element selected from tungsten, molybdenum, and niobium can be used.

[0088] As described above, when the anion dopant and the M3-containing dopant are used in combination during calcination of the oxide precursor to simultaneously dope the primary particles and induce growth of the primary particles, the shape of the primary particles becomes closer to a sphere, and the porosity of the secondary particles formed by aggregation of the primary particles can be reduced.

[0089] When the porosity in the lithium manganese-based oxide is reduced, the capacity per unit volume can be increased, and the insufficient electrochemical properties of the positive electrode active material including the lithium manganese-based oxide can be compensated for.

[0090] Specifically, the interparticle porosity between the primary particles, which can be measured from a cross-sectional SEM image of the secondary particles, may be 10% or less, preferably 5% or less. By reducing the interparticle porosity between the primary particles in the secondary particles, the energy density per unit volume of the lithium manganese oxide can be improved.

[0091] In addition, when the anion dopant and the M3-containing dopant are used in combination during calcination of the oxide precursor to simultaneously dope the primary particles and induce the growth of the primary particles, it is particularly effective in reducing the porosity at the surface of the secondary particles.

[0092] For example, when the distance from the center of the secondary particle determined from the cross-sectional SEM image of the secondary particle to the surface of the secondary particle is referred to as r, the surface portion of the secondary particle can be defined as an outer bulk region that is a region that is 0.5r to 1.0r away from the center of the secondary particle. In this case, the porosity in the outer bulk region that can be measured from the cross-sectional SEM image of the secondary particle may be 1% or less, preferably 0.72% or less.

[0093] The improvement in the porosity in the lithium manganese-based oxide may also have a positive effect on the improvement of the BET specific surface area and the compressed density of the positive electrode active material including the lithium manganese-based oxide.

[0094] The lithium manganese oxide defined in this application is 2.0m 2 More specifically, the lithium manganese-based oxide may have a specific surface area of ​​2.0 m / g or less by simultaneously doping the primary particles and inducing the growth of the primary particles by using the anion dopant and the M3-containing dopant in combination during the calcination of the oxide precursor. 2 / g or less, preferably 0.3m 2 / g or more 2.0m 2 / g or less, more preferably 0.3m 2 / g or more 1.1m 2 The nanoparticles may have a BET specific surface area of ​​0.1 to 1.0 μm / g or less.

[0095] Furthermore, when the positive electrode active material containing the lithium manganese oxide is compressed under a pressure of 4.5 tons, the press density is greater than 2.53 g / cc, and preferably, the compressed density is 2.58 g / cc or more.

[0096] The lithium manganese-based oxide represented by Formula 1 may selectively contain cobalt. When the lithium manganese-based oxide contains cobalt, the mole fraction of the cobalt relative to the moles of all metal elements in the lithium manganese-based oxide may be 20% or less, preferably 15% or less, and more preferably 10% or less. In other cases, the lithium manganese-based oxide represented by Formula 1 may have a cobalt-free composition that does not contain cobalt.

[0097] The Li / Metal molar ratio measured from the lithium manganese-based oxide represented by Chemical Formula 1 may be greater than 1, preferably 1.1 to 1.7, and more preferably 1.2 to 1.6. When the Li / Metal molar ratio measured from the lithium manganese-based oxide has a value greater than 1, it is possible to form a lithium-excess lithium manganese-based oxide. In addition, in order for the lithium manganese-based oxide to appropriately form a solid solution in which a phase belonging to the C2 / m space group and a phase belonging to the R3-m space group are solid-dissolved or combined, and to exhibit high capacity under a high-voltage operating environment, the Li / Metal molar ratio of the lithium manganese-based oxide is preferably 1.2 to 1.6.

[0098] In order to properly form a solid solution or a composite solid solution of a phase belonging to the C2 / m space group and a phase belonging to the R3-m space group, the content of manganese among all metal elements excluding lithium present in the lithium manganese-based oxide represented by Chemical Formula 1 is preferably 50 mol % or more. In order that the lithium manganese-based oxide may have the OLO characteristic of exhibiting high capacity in a high voltage operating environment, the content of manganese among all metal elements excluding lithium present in the lithium manganese-based oxide is more preferably 50 mol % or more and less than 80 mol %, and even more preferably 55 mol % to 75 mol %.

[0099] When the manganese content of the lithium manganese-based oxide exceeds 80 mol%, a phase transition may occur due to the movement of transition metals (especially manganese) in the lithium manganese-based oxide during formation and / or operation of the lithium secondary battery. Such a phase transition forms a spinel phase, and the spinel phase acting as an impurity in the lithium manganese-based oxide may cause a decrease in charge / discharge capacity or voltage decay during the charge / discharge cycle of the lithium secondary battery.

[0100] In order to properly form a solid solution in which a phase belonging to the C2 / m space group and a phase belonging to the R3-m space group are dissolved or combined, the content of nickel among all metal elements excluding lithium present in the lithium manganese-based oxide represented by Chemical Formula 1 is preferably less than 50 mol%.

[0101] When the nickel content in the lithium manganese-based oxide is 50 mol % or more, the C2 / m phase may not be sufficiently formed, or the phase belonging to the C2 / m space group and the phase belonging to the R3-m space group may not form a sufficient solid solution, which may cause phase separation during formation and / or operation of the lithium secondary battery.

[0102] In general, commercially available ternary lithium composite oxides having a nickel-cobalt-manganese (NCM) or nickel-cobalt-aluminum (NCA) composition exist in a single phase belonging to the R3-m space group.

[0103] Meanwhile, the lithium-rich lithium manganese oxide represented by the formula 1 is rLi2MnO 3-b′ X′ b′ The oxides of the phase belonging to the C2 / m space group represented by a M1 x M2 y M3 z O 2-b X b The lithium manganese-based oxide exists as a composite oxide in which an oxide of the C2 / m phase and an oxide of the R3-m phase form a solid solution. For example, the lithium manganese-based oxide may exist in a state in which an oxide of the C2 / m phase and an oxide of the R3-m phase form a solid solution.

[0104] In this case, a complex oxide in which a phase belonging to the C2 / m space group and a phase belonging to the R3-m space group are simply physically and / or chemically bonded or attached does not fall under the category of a solid solution as defined in this application.

[0105] For example, a composite oxide having a phase belonging to the C2 / m space group, in which a metal oxide having a phase belonging to the C2 / m space group and a metal oxide having a phase belonging to the R3-m space group are mixed and the surface of the composite oxide is coated with a metal oxide having a phase belonging to the R3-m space group, does not fall under the category of a solid solution as defined in the present application.

[0106] In the lithium manganese-based oxide represented by the formula 1, when r exceeds 0.7, the lithium manganese-based oxide is a C2 / m phase oxide, Li2MnO 3-b′ X′ b′ In other words, in order to sufficiently activate the C2 / m phase oxide, which has a relatively high resistance among the lithium manganese-based oxides, and improve the surface kinetics, it is preferable that the R3-m phase oxide is present at a certain ratio or more.

[0107] Lithium secondary battery According to another aspect of the present invention, there is provided a positive electrode including a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector, wherein the positive electrode active material layer may include the lithium manganese-based oxide according to the various embodiments of the present invention as a positive electrode active material.

[0108] Therefore, a detailed description of the lithium manganese-based oxide will be omitted, and only the remaining components not described above will be described below. Also, for convenience, the lithium manganese-based oxide will be referred to as a positive electrode active material hereinafter.

[0109] The positive electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has conductivity, and may be, for example, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. The positive electrode current collector may usually have a thickness of 3 to 500 μm, and fine irregularities may be formed on the surface of the current collector to increase the adhesive strength of the positive electrode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0110] The positive electrode active material layer may be prepared by coating a positive electrode slurry composition containing the positive electrode active material, a conductive material, and optionally a binder, on the positive electrode current collector.

[0111] At this time, the positive electrode active material may be included in a content of 80 wt% to 99 wt%, more specifically, 85 wt% to 98.5 wt%, based on the total weight of the positive electrode active material layer, and excellent capacity characteristics can be exhibited when the content is within this range, but is not necessarily limited thereto.

[0112] The conductive material is used to impart conductivity to the electrode, and can be used without any particular limitation as long as it has electronic conductivity without causing chemical changes in the battery that is constructed. Specific examples include graphite such as natural graphite and artificial graphite, carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, carbon-based materials such as carbon fibers, metal powders or metal fibers such as copper, nickel, aluminum, and silver, conductive whiskers such as zinc oxide and potassium titanate, conductive metal oxides such as titanium oxide, and conductive polymers such as polyphenylene derivatives, and the like, and one or more of these may be used alone or in combination. The conductive material may be contained in an amount of 0.1 wt% to 15 wt% based on the total weight of the positive electrode active material layer.

[0113] The binder serves to improve the adhesion between the positive electrode active material particles and the adhesive strength between the positive electrode active material and the current collector. Specific examples include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated-EPDM, styrene-butadiene rubber (SBR), fluororubber, and various copolymers thereof, and among these, one type alone or a mixture of two or more types may be used. The binder may be included in an amount of 0.1 to 15 wt% based on the total weight of the positive electrode active material layer.

[0114] The positive electrode may be manufactured by a typical method for manufacturing a positive electrode, except for using the positive electrode active material. Specifically, the positive electrode may be manufactured by dissolving or dispersing the positive electrode active material and, optionally, a binder and a conductive material in a solvent to prepare a positive electrode slurry composition, which is then coated on a positive electrode current collector, followed by drying and rolling.

[0115] The solvent may be a solvent commonly used in the art, such as dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone, or water, and one or more of these may be used alone or in combination. The amount of the solvent used is sufficient to dissolve or disperse the positive electrode active material, conductive material, and binder, and to provide a viscosity that allows excellent thickness uniformity when applied to manufacture a positive electrode, taking into consideration the coating thickness of the slurry and the production yield.

[0116] In another embodiment, the positive electrode may be manufactured by casting the positive electrode slurry composition on a separate support, peeling the positive electrode slurry composition from the support, and laminating the resulting film on a positive electrode current collector.

[0117] According to yet another aspect of the present invention, there may be provided an electrochemical device including the above-mentioned positive electrode. The electrochemical device may be, for example, a battery or a capacitor, and more specifically, a lithium secondary battery.

[0118] Specifically, the lithium secondary battery may include a positive electrode, a negative electrode facing the positive electrode, and a separator and an electrolyte interposed between the positive electrode and the negative electrode. Here, since the positive electrode is as described above, a detailed description thereof will be omitted for convenience, and only the remaining components not described above will be described in detail below.

[0119] The lithium secondary battery may optionally further include a battery container that houses an electrode assembly of the positive electrode, the negative electrode, and the separator, and a sealing member that seals the battery container.

[0120] The negative electrode may include a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector.

[0121] The negative electrode current collector is not particularly limited as long as it has high conductivity without inducing chemical changes in the battery, and may be, for example, copper, stainless steel, aluminum, nickel, titanium, baked carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, or aluminum-cadmium alloy. The negative electrode current collector may generally have a thickness of 3 μm to 500 μm, and like the positive electrode current collector, the surface of the current collector may be formed with fine irregularities to strengthen the binding force of the negative electrode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, or nonwoven fabric.

[0122] The negative electrode active material layer may be prepared by coating a negative electrode slurry composition containing the negative electrode active material, a conductive material, and optionally a binder, on the negative electrode current collector.

[0123] The negative electrode active material may be a compound capable of reversible intercalation and deintercalation of lithium. Specific examples of the negative electrode active material include carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon, metallic compounds capable of alloying with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, and Al alloys, and SiO β (0<β<2), metal oxides capable of doping and dedoping lithium, such as SnO2, vanadium oxide, and lithium vanadium oxide, or composites containing the metallic compounds and carbonaceous materials, such as Si-C composites and Sn-C composites, may be used. A metallic lithium thin film may be used as the negative electrode active material. Low-crystalline carbon and high-crystalline carbon may both be used as the carbon material. Representative examples of low crystalline carbon include soft carbon and hard carbon, and representative examples of high crystalline carbon include amorphous, plate-like, flake-like, spherical or fibrous natural graphite or artificial graphite, kish graphite, pyrolytic carbon, mesophase pitch based carbon fiber, carbon microbeads, mesophase pitches, and high-temperature fired carbon such as petroleum or coal tar pitch derived cokes.

[0124] The negative electrode active material may be included in an amount of 80 wt % to 99 wt % based on the total weight of the negative electrode active material layer.

[0125] The binder is a component that aids in bonding between the conductive material, the active material, and the current collector, and may be added in an amount of 0.1 wt% to 10 wt% based on the total weight of the negative electrode active material layer. Examples of such binders include polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene-butadiene rubber, nitrile-butadiene rubber, fluororubber, and various copolymers thereof.

[0126] The conductive material may be added as a component for further improving the conductivity of the negative electrode active material in an amount of 10 wt% or less, preferably 5 wt% or less, based on the total weight of the negative electrode active material layer. Such a conductive material is not particularly limited as long as it has conductivity without inducing a chemical change in the battery, and may be, for example, graphite such as natural graphite or artificial graphite, carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, or thermal black, conductive fibers such as carbon fibers or metal fibers, metal powders such as carbon fluoride, aluminum, or nickel powder, conductive whiskers such as zinc oxide or potassium titanate, conductive metal oxides such as titanium oxide, or conductive materials such as polyphenylene derivatives.

[0127] In one embodiment, the negative electrode active material layer may be prepared by coating a negative electrode slurry composition prepared by dissolving or dispersing a negative electrode active material, and optionally a binder and a conductive material, in a solvent on a negative electrode current collector and drying the coating. Alternatively, the negative electrode slurry composition may be cast on a separate support, and then peeled off from the support to obtain a film, which may be laminated on the negative electrode current collector.

[0128] In another embodiment, the negative electrode active material layer may be manufactured by coating a negative electrode slurry composition prepared by dissolving or dispersing a negative electrode active material, and optionally a binder and a conductive material, in a solvent on a negative electrode current collector and drying the coating, or by casting the negative electrode slurry composition on a separate support and peeling the composition from the support to obtain a film, which may be laminated on the negative electrode current collector.

[0129] Meanwhile, in the lithium secondary battery, the separator separates the negative electrode and the positive electrode to provide a path for lithium ions to move. Any separator that is generally used as a separator in a lithium secondary battery may be used without any particular limitation. In particular, it is preferable that the separator has low resistance to ion movement of the electrolyte and has excellent electrolyte humidification ability. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin-based polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof may be used. In addition, a conventional porous nonwoven fabric, for example, a nonwoven fabric made of high-melting point glass fiber, polyethylene terephthalate fiber, etc. may be used. In addition, in order to ensure heat resistance or mechanical strength, a coated separator containing a ceramic component or a polymer material may be used, and may be selectively used as a single layer or multilayer structure.

[0130] In addition, examples of the electrolyte used in the present invention include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in the production of lithium secondary batteries, but are not limited to these.

[0131] Specifically, the electrolyte may include an organic solvent and a lithium salt.

[0132] The organic solvent may be used without any particular limitation as long as it serves as a medium through which ions involved in the electrochemical reaction of the battery can move. Specifically, the organic solvent may be an ester solvent such as methyl acetate, ethyl acetate, γ-butyrolactone, or ε-caprolactone, an ether solvent such as dibutyl ether or tetrahydrofuran, a ketone solvent such as cyclohexanone, an aromatic hydrocarbon solvent such as benzene or fluorobenzene, dimethylcarbonate (DMC), diethylcarbonate (DEC), methylethylcarbonate (MEC), ethylmethylcarbonate (EMC), ethylene carbonate (EC), or propylene carbonate (propylene carbonate). Examples of the solvents that may be used include carbonate-based solvents such as ethylene carbonate (PC), alcohol-based solvents such as ethyl alcohol and isopropyl alcohol, nitriles such as R-CN (R is a straight-chain, branched or cyclic hydrocarbon group having 2 to 20 carbon atoms, which may contain a double bond aromatic ring or an ether bond), amides such as dimethylformamide, dioxolanes such as 1,3-dioxolane, and sulfolanes. Among these, carbonate-based solvents are preferred, and a mixture of a cyclic carbonate (e.g., ethylene carbonate or propylene carbonate) having high ionic conductivity and high dielectric constant that can improve the charge / discharge performance of a battery and a low-viscosity linear carbonate compound (e.g., ethyl methyl carbonate, dimethyl carbonate or diethyl carbonate) is more preferred. In this case, the performance of the electrolyte may be excellent if the cyclic carbonate and the chain carbonate are mixed at a volume ratio of about 1:1 to about 1:9.

[0133] The lithium salt may be used without any particular limitation as long as it is a compound capable of providing lithium ions used in a lithium secondary battery. Specifically, the lithium salt may be LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3), LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, or LiB(C2O4)2. The concentration of the lithium salt is preferably within the range of 0.1 to 2.0M. When the concentration of the lithium salt is within the above range, the electrolyte has appropriate conductivity and viscosity, so that excellent electrolyte performance can be exhibited and lithium ions can be effectively transferred.

[0134] When the electrolyte used in the present application is a solid electrolyte, for example, a solid inorganic electrolyte such as a sulfide-based solid electrolyte, an oxide-based solid electrolyte, a nitride-based solid electrolyte, or a halide-based solid electrolyte may be used, and preferably, a sulfide-based solid electrolyte may be used.

[0135] As the sulfide-based solid electrolyte material, a solid electrolyte containing Li, an X element (wherein X is at least one selected from P, As, Sb, Si, Ge, Sn, B, Al, Ga, and In) and S may be used. Examples of the sulfide-based solid electrolyte material include Li2S-P2S5, Li2S-P2S-LiX (wherein X is a halogen element such as I or Cl), Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, Li2S-P2S5-Z m S n (where m and n are integers, and Z is Ge, Zn, or Ga.), Li2S-GeS2, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li p MO q(wherein p and q are integers and M is P, Si, Ge, B, Al, Ga or In).

[0136] The solid electrolyte, preferably the sulfide-based solid electrolyte, may be amorphous or crystalline, or may be in a mixed amorphous and crystalline state.

[0137] The oxide-based solid electrolyte material is Li7La3Zr2O 12 , Li 7-x La3Zr 1-x Nb x O 12 , Li 7-3x La3Zr2Al x O 12 , Li 3x La 2 / 3-x TiO3, Li 1+x Al x Ti 2-x (PO4)3, Li 1+x Al x Ge 2-x (PO4)3, Li3PO4, Li 3+x PO 4-x N x (LiPON), Li 2+2x Zinc 1-x Examples include GeO4 (LISICON).

[0138] The solid electrolyte may be disposed as a separate layer (solid electrolyte layer) between the positive electrode and the negative electrode. The solid electrolyte may be partially included in the positive electrode active material layer of the positive electrode, independent of the solid electrolyte layer, or the solid electrolyte may be partially included in the negative electrode active material layer of the negative electrode, independent of the solid electrolyte layer.

[0139] In addition to the electrolyte components, the electrolyte may further contain one or more additives such as haloalkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, or aluminum trichloride, for the purpose of improving the life characteristics of the battery, suppressing the decrease in battery capacity, improving the discharge capacity of the battery, etc. In this case, the additives may be contained in an amount of 0.1 to 5 wt% based on the total weight of the electrolyte.

[0140] As described above, the lithium secondary battery including the positive electrode active material according to the present invention stably exhibits excellent discharge capacity, output characteristics and life characteristics, and is therefore useful in the fields of portable devices such as mobile phones, notebook computers, and digital cameras, and electric vehicles such as hybrid electric vehicles (HEVs).

[0141] The external shape of the lithium secondary battery according to the present invention is not particularly limited, and may be a cylindrical shape using a can, a square shape, a pouch shape, a coin shape, etc. Furthermore, the lithium secondary battery can be used not only as a battery cell used as a power source for a small device, but also preferably as a unit battery for a medium- to large-sized battery module including a plurality of battery cells.

[0142] According to yet another aspect of the present invention, there may be provided a battery module including the lithium secondary battery as a unit cell and / or a battery pack including the same.

[0143] The battery module or the battery pack can be used as a power source for one or more medium- to large-sized devices, such as a power tool, an electric vehicle (Electric Vehicle (EV), a hybrid electric vehicle, and a plug-in hybrid electric vehicle (PHEV), or a power storage system.

[0144] The present invention will be described in more detail below with reference to examples. However, these examples are for the purpose of illustrating the present invention, and the scope of the present invention is not to be construed as being limited by these examples.

[0145] Production Example 1. Production of positive electrode active material Example 1 (a) Preparation of precursor The reactor was filled with an aqueous solution of NiSO4·6H2O and MnSO4·H2O in a molar ratio of 40:60, and NaOH and NH4OH were added while stirring. The temperature inside the reactor was kept at 45°C, and the precursor synthesis reaction was carried out while N2 gas was added to the reactor. After the reaction was completed, the reactor was washed and dehydrated, and the Ni 0.4 Mn 0.6 A hydroxide precursor with the composition (OH)2 was obtained.

[0146] (b) First heat treatment The temperature of the calcination furnace in an O2 atmosphere was increased at a rate of 2°C / min, and the hydroxide precursor obtained in the above step (a) was heat-treated for 5 hours while maintaining the temperature at 550°C. The hydroxide precursor was then cooled in the furnace to obtain a precursor in an oxide state.

[0147] (c) Second heat treatment A mixture was prepared by mixing the oxide precursor obtained in the step (b), LiOH (Li / Metal molar ratio=1.25) as a lithium source material, LiF weighed out so that the content of fluorine (F) based on metal elements excluding lithium in the precursor was 1.0 mol%, and WO3 weighed out so that the content of tungsten (W) based on metal elements excluding lithium in the precursor was 0.75 mol%.

[0148] Next, the temperature of a sintering furnace in an O2 atmosphere was increased at a rate of 2°C / min, and the mixture was heat-treated for 8 hours while being kept at 850°C. The mixture was then cooled in the furnace, classified and crushed to obtain the final product, a positive electrode active material containing lithium manganese oxide (average particle size 4.0 μm).

[0149] Example 2 A positive electrode active material (average particle size: 4.0 μm) was prepared in the same manner as in Example 1, except that the heat treatment temperature in the step (c) was 900° C. instead of 850° C.

[0150] Example 3 A positive electrode active material (average particle size: 4.0 μm) was prepared in the same manner as in Example 1, except that the heat treatment temperature in the step (c) was 950° C. instead of 850° C.

[0151] Example 4 A positive electrode active material (average particle size 4.0 μm) was prepared in the same manner as in Example 1, except that in step (c), MoO 3 was used instead of WO 3 , and the heat treatment temperature was 900° C. instead of 850° C.

[0152] Example 5 A positive electrode active material (average particle size 4.0 μm) was prepared in the same manner as in Example 1, except that in step (c), Nb2O5 was used instead of WO3, and the heat treatment temperature was 900° C. instead of 850° C.

[0153] Comparative Example 1 A positive electrode active material (average particle size: 4.0 μm) was produced in the same manner as in Example 1, except that LiF and WO 3 were not mixed in the step (c).

[0154] Comparative Example 2 A positive electrode active material (average particle size: 4.0 μm) was produced in the same manner as in Example 1, except that LiF was not mixed in the step (c).

[0155] Comparative Example 3 A positive electrode active material (average particle size: 4.0 μm) was prepared in the same manner as in Example 1, except that WO 3 was not mixed in the step (c).

[0156] Comparative Example 4 A positive electrode active material (average particle size 4.0 μm) was produced in the same manner as in Example 1, except that LiF and WO 3 were not mixed in step (c) and the heat treatment temperature was 1,000° C. instead of 850° C.

[0157] Comparative Example 5 A positive electrode active material (average particle size 4.0 μm) was produced in the same manner as in Example 1, except that LiF weighed out to be 0.1 mol % and WO3 weighed out to be 0.1 mol % were mixed in the step (c).

[0158] Composition of lithium manganese oxide The composition (molar ratio of each element) of the lithium manganese-based oxide contained in each of the positive electrode active materials prepared in Preparation Example 1 was measured through ICP analysis.

[0159] The measurement results are shown in Table 1 below.

[0160] [Table 1] *Li / Metal Molar ratio indicates the molar ratio of lithium to all elements other than lithium in the lithium manganese-based oxide. *The element content (mol%) is calculated based on the total elements other than lithium in the lithium manganese oxide.

[0161] Manufacturing Example 2. Manufacturing of lithium secondary batteries A positive electrode slurry was prepared by dispersing 90 wt% of the positive electrode active material prepared in Preparation Example 1, 4.5 wt% of carbon black, and 5.5 wt% of PVDF binder in N-methyl-2-pyrrolidone (NMP). The positive electrode slurry was uniformly applied to an aluminum thin film having a thickness of 15 μm and dried in a vacuum at 135° C. to prepare a positive electrode for a lithium secondary battery.

[0162] A half cell was fabricated using a lithium foil as a counter electrode for the positive electrode, a porous polyethylene film (Celgard 2300, thickness: 25 μm) as a separator, and an electrolyte of LiPF6 at a concentration of 1.15 M in a solvent of ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate mixed in a volume ratio of 2:4:4.

[0163] Experimental Example 1. Structural analysis of positive electrode active material (1) Secondary particle-type lithium manganese-based oxide was separated from each of the positive electrode active materials prepared in Preparation Example 1, and then photographed using a scanning electron microscope to obtain SEM images.

[0164] Next, one secondary particle was selected from the SEM image using the Image analyzer program, and 20 primary particles were selected in order of the longest short axis length from among the primary particles exposed on the surface of the secondary particle, and the long axis length and short axis length of each were measured. From the measurement results, the average long axis length A of the primary particles, the minimum long axis length B of the primary particles, the maximum long axis length C of the primary particles, the average short axis length D of the primary particles, the minimum short axis length E of the primary particles, the maximum short axis length F of the primary particles, and the average particle size G of the primary particles ([long axis length + short axis length] / 2) were calculated.

[0165] (2) In addition, each of the lithium manganese-based oxides (secondary particles) was processed to prepare a cross section using a cross-section Polisher (accelerating voltage 5.0 kV, milling for 4 hours), and then photographed using a scanning electron microscope to obtain a cross-sectional SEM image.

[0166] Next, the number of pores H was counted from the cross section of the secondary particle in the cross-sectional SEM image using the Image Analyzer program, and the cross-sectional porosity I was calculated.

[0167] The cross-sectional porosity I was calculated by binarizing the cross-sectional SEM image and then calculating the ratio of the sum of the area of ​​all voids present in the secondary particles to the total area of ​​the cross section of the secondary particles ([sum of the area of ​​all voids present in the secondary particles / total area of ​​the cross section of the secondary particles] / 100).

[0168] In addition, the center of the secondary particle was set from the binarized cross-sectional SEM image, and the distance from the center of the secondary particle to the surface of the secondary particle was defined as r. The region with a distance of 0.5r to 1.0r from the center of the secondary particle was defined as an outer bulk region.

[0169] The external bulk porosity J ([sum of all void areas present in the external bulk region / total area of ​​the external bulk region] × 100) was calculated by dividing the sum of all void areas present in the external bulk region by the total area of ​​the cross section of the external bulk region.

[0170] (3) The BET specific surface area K was calculated from the amount of nitrogen gas adsorbed by the lithium manganese oxide at liquid nitrogen temperature (77 K) using a specific surface area measurement device based on a gas adsorption method (MicrotaracBEL's BELSORP-miniII).

[0171] (4) 3 g of each of the positive electrode active materials produced in Production Example 1 was weighed out and placed in a pelletizer, and then pressed at 4.5 tons for 5 seconds, and the compressed density L was measured.

[0172] The measurement results are shown in Tables 2 and 3 below.

[0173] [Table 2]

[0174] [Table 3]

[0175] Comparing the lithium manganese-based oxide contained in the positive electrode active material according to Example 1 (an example in which co-doping of tungsten and fluorine was induced when the oxide precursor was calcined) and Comparative Example 1 (an example prepared under the same conditions as Example 1 except that co-doping of tungsten and fluorine was not induced when the oxide precursor was calcined), it can be seen that co-doping of tungsten and fluorine induced the growth of the long axis length and short axis length of the primary particles when the oxide precursor was calcined.

[0176] It can also be seen that the cross-sectional porosity I and external bulk porosity J of the lithium manganese-based oxide according to Example 1 are smaller than those of the lithium manganese-based oxide according to Comparative Example 1. It can also be seen that such a difference affects the BET specific surface area K and compressed density L of the positive electrode active material including the lithium manganese-based oxide according to Example 1 and the positive electrode active material according to Comparative Example 1.

[0177] Comparing the lithium manganese-based oxides contained in the positive electrode active materials according to Example 2 (an example in which co-doping of tungsten and fluorine was induced when the oxide precursor was calcined) and Comparative Example 2 (an example prepared under the same conditions as Example 2 except that only tungsten doping was induced when the oxide precursor was calcined), it can be seen that co-doping of tungsten and fluorine when the oxide precursor was calcined had a more significant effect on the growth of the major axis length and minor axis length of the primary particles than doping with tungsten alone.

[0178] Similarly, in the case of Examples 4 and 5, in which the co-doping sources were different from those of Examples 1 to 3, it was confirmed that the co-doping of molybdenum and fluorine or the co-doping of niobium and fluorine induced the growth of the long axis length and short axis length of the primary particles while reducing the cross-sectional porosity and external bulk porosity.

[0179] In addition, referring to the results of Comparative Example 4 in which the calcination temperature of the oxide precursor was increased to 1,000°C, it can be seen that the growth of primary particles was generally induced, but the effect of reducing the external bulk porosity was insufficient compared to the Examples.

[0180] In addition, even though raw materials for simultaneous doping with tungsten and fluorine are used during calcination of the oxide precursor, the content of the raw materials is too low in Comparative Example 5, and it can be seen that the growth of the primary particles is hardly induced.

[0181] Experimental Example 2: Evaluation of the electrochemical properties of lithium secondary batteries The lithium secondary battery (half cell) manufactured in Manufacturing Example 2 was subjected to a charge-discharge experiment at 25° C., voltage range of 2.0 V to 4.6 V, and discharge rate of 0.1 C to 5.0 C using an electrochemical analyzer (Toyo, Toscat-3100) to measure the initial charge capacity, initial discharge capacity, capacity per volume, initial reversible efficiency, and rate capability (rate capability (C-rate)). The capacity per volume was calculated by multiplying the initial discharge capacity by the compaction density (L in Table 3).

[0182] In addition, the same lithium secondary battery was charged and discharged 50 times at 25°C and within a driving voltage range of 2.0V to 4.6V at 1C / 1C, and then the ratio of the discharge capacity at the 50th cycle to the initial discharge capacity (cycle capacity retention) was measured.

[0183] The measurement results are shown in Table 4 below.

[0184] [Table 4]

[0185] Referring to the results in Table 4, it can be seen that the lithium secondary battery using the positive electrode active material including the lithium manganese-based oxide according to Example 1 (which induces simultaneous doping of tungsten and fluorine when the oxide precursor is calcined) has higher initial charge capacity, initial discharge capacity, discharge capacity ratio, and cycle capacity retention rate than the lithium secondary battery using the positive electrode active material including the lithium manganese-based oxide according to Comparative Example 1 (which does not induce simultaneous doping of tungsten and fluorine when the oxide precursor is calcined). In particular, it can be seen that the capacity per unit volume of Example 1 is significantly improved compared to Comparative Example 1.

[0186] In addition, referring to the results of Comparative Example 2 in which tungsten was selectively doped during calcination of the oxide precursor, it can be seen that although the initial charge capacity and initial discharge capacity were at similar levels to those of the Examples, the capacity per unit volume and cycle capacity retention rate were lower than those of the Examples.

[0187] Similarly, when looking at the results of Comparative Example 3 in which fluorine was selectively doped during calcination of the oxide precursor, it can be seen that the capacity per unit volume and the rate characteristics were lower than those of the Examples.

[0188] In addition, in the case of Comparative Example 4, where the calcination temperature of the oxide precursor was increased to 1,000°C, the overall growth of primary particles was induced to a similar level to that of the Examples, but the initial charge capacity, initial discharge capacity, capacity per unit volume, and rate of discharge capacity were lower than those of the Examples. It is expected that the above results are due to the deterioration caused by thermal damage to the lithium manganese-based oxide due to the excessively high calcination temperature during the second heat treatment. In particular, it can be confirmed that the initial discharge capacity is excessively lower than that of the Examples, showing a large difference in capacity per unit volume.

[0189] In addition, even though raw materials for simultaneous doping with tungsten and fluorine were used during calcination of the oxide precursor, in Comparative Example 5 in which the amount of the raw materials was excessively small, it was confirmed that the initial charge capacity, initial discharge capacity, capacity per volume, discharge capacity ratio, and cycle capacity retention rate were lower than those of Example 1.

[0190] Although the embodiments of the present invention have been described above, a person having ordinary knowledge in the art may modify and change the present invention in various ways by adding, changing, deleting or adding elements without departing from the concept of the present invention described in the claims, and this may also be considered to be within the scope of the claims of the present invention.

Claims

1. A positive electrode active material comprising a lithium manganese-based oxide in which a phase belonging to a C2 / m space group and a phase belonging to an R3-m space group are dissolved or combined, The lithium manganese-based oxide includes secondary particles formed by agglomeration of a plurality of primary particles, The lithium manganese-based oxide contains at least one selected from tungsten, molybdenum, and niobium as a dopant, and at least a portion of oxygen present in the lithium manganese-based oxide is substituted with a halogen; a porosity between the primary particles measured from a cross-sectional SEM image of the secondary particles is 10% or less.

2. The distance from the center of the secondary particle determined from the cross-sectional SEM image of the secondary particle to the surface of the secondary particle is referred to as r, and a region having a distance of 0.5r to 1.0r from the center of the secondary particle is referred to as an outer bulk region.

10. The cathode active material of claim 1, wherein the exterior bulk region has a porosity of 1% or less.

3. 2 . The positive electrode active material according to claim 1 , wherein an average value of the minor axis length of the primary particles exposed on the surfaces of the secondary particles is 160 nm or more and 500 nm or less.

4. 2 . The positive electrode active material according to claim 1 , wherein the minimum value of the minor axis length measured for the primary particles exposed on the surface of the secondary particles is 80 nm or more.

5. 2 . The positive electrode active material according to claim 1 , wherein the maximum minor axis length measured for the primary particles exposed on the surfaces of the secondary particles is 1 μm or less.

6. 2 . The positive electrode active material according to claim 1 , wherein an average value of the major axis length of the primary particles exposed on the surfaces of the secondary particles is 570 nm or more and 1 μm or less.

7. 2 . The positive electrode active material according to claim 1 , wherein the minimum value of the major axis length measured for the primary particles exposed on the surface of the secondary particles is 245 nm or more.

8. 2 . The positive electrode active material according to claim 1 , wherein the maximum major axis length measured for the primary particles exposed on the surfaces of the secondary particles is 1.5 μm or less.

9. 2. The positive electrode active material according to claim 1, wherein the average value ([long axis length + short axis length] / 2) of the long axis length and the short axis length of the primary particles exposed on the surface of the secondary particles is 0.1 μm to 5 μm.

10. The positive electrode active material of claim 1 , wherein the lithium manganese-based oxide is represented by the following Chemical Formula 1: [Chemical formula 1] rLi 2 MnO 3-b′ X′ b′ ・(1-r)Li a M1 x M2 y M3 z O 2-b X b (where: M1 is at least one selected from Ni and Mn; M2 is at least one selected from Ni, Mn, Co, Al, P, Nb, B, Ti, Zr, Ba, K, Mo, Si, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, V, Ta, Sn, Hf, Ce, Gd and Nd; M3 is at least one selected from W, Mo, and Nb; M1 to M3 do not overlap with each other, X and X' are halogens capable of substituting at least a portion of the oxygen present in the lithium manganese oxide, 0<r≦0.7, 0<a≦1, 0≦b≦0.1, 0≦b'≦0.1, 0<x≦1, 0≦y<1, 0<z≦0.1, and 0<x+y+z≦1, with the proviso that b and b' are not both 0.

11. The cathode active material of claim 10 , wherein the primary particles are doped with fluorine.

12. The BET specific surface area of ​​the secondary particles is 0.3 m 2 / g or more 2.0m 2 The positive electrode active material according to claim 1 , wherein the CdTe content is 1 / g or less.

13. 2. The cathode active material of claim 1, wherein the pressed density of the cathode active material when compressed under a pressure of 4.5 tons is greater than 2.53 g / cc.

14. A positive electrode comprising the positive electrode active material according to claim 1 .

15. A lithium secondary battery using the positive electrode according to claim 14.

Citation Information

Patent Citations

  • Cathode active material, and battery

    JP2020202172A

  • Cathode active material and lithium secondary battery comprising same

    WO2022119157A1